Saint Lucia. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in Saint Lucia during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as family farming, sustainability, governance, financing, exports, resilience against climate change and improving production chains for vegetables, cocoa, roots and tubers. Technical cooperation was also provided for the use of school gardens and a virtual business incubator (VBI), a resource network, and an acceleration center to support youth entrepreneurship. Finally, support was given to the inclusion of women in agricultural processes.